Knowledge, attitudes, and practice regarding medication use in pregnant women in Southern Italy - Navaro, Monica (PLoS One, 2018)
The study assessed knowledge, attitudes, and medication use of a random sample of pregnant women attending outpatient Gynecology and Obstetrics clinics at randomly selected public General and Teaching hospitals in Naples, Italy. A total of 503 women participated. Those more likely to know that a pregnant woman with chronic condition must discuss whether or not to take a medication with the physician were Italian, aged 31–40 years, employed, with no history of abortion, having had a medical problem within the previous year, with a better self-perceived health status, who knew how to use medications during pregnancy, and who needed information on medications. The knowledge of the potential risk of using non-prescribed medications during pregnancy was significantly higher in employed women, who received information from physicians, who knew how to use medications during pregnancy, and who knew the possible damages related to medications use. More than half had used at least one medication. Those aged 26–35 years, Italian, non-graduated, in the third trimester, having had a medical problem within the previous year, with a risky pregnancy, and with a knowledge that women with chronic condition must discuss whether or not to take a medication with the physician were more likely to use medication. Less than half had used medication without a physician’s advice. Those who were more likely to self-medicate were older, Italian, multiparous, with no history of abortion, who knew that women with chronic condition must discuss whether or not to take a medication with the physician, who did not know the potential risk of using non-prescribed medication during pregnancy, who had used prescribed medication during pregnancy, and who needed information about medications. Educational programs for women about medication use are important to increase their knowledge of the potential risks to the pregnant women and the unborn child in order to reduce self-medication.